A institucionalização da responsabilidade social empresarial em uma indústria localizada no estado do Ceará - Martins, Otiliana Farias (2010)
This work tells about the issue of the social responsibility under the lenses of the institutional theory. It’s main objective is to investigate how the process of institutionalization of the social responsibility happened at Marisol Industry, winner of the 13th SESI Work Quality Award in 2006.The theoretic referral developed is divided into two parts: first, the Corporate Social Responsibility and second, the Institutional Approach. According to the objectives, this is a searched/descriptive, and according to the methodological process it is a bibliographicdocumental and a field survey conducted through a case study. Interviews and questionnaires were applied for the data collection and social/finance balance sheets were analyzed. As concerned as the data nature, the research is qualitative. The results show that the process of institutionalization of the industry researched happened in a gradually way, considering that the two first phases were more consolidated respectful to the habitualness and objectiveness due to the settlement phase needs to be more consolidated. In this sense the data aims to the evidence of the social responsibility practices continuity, even with the nonresistance of the employees during the implementation of social responsibility actions the institutionalization process does not occurred completely. The industry needs to reinforce more wide proposals for the social responsibility field and apply them to its strategic objectives.